Board Characterstics and Firm Performance: Case of Saudi Arabia - Ghabayen, Mohammad Ahid Mohammad (2012)
Corporate governance (CG) has received much attention in the current studies all over the world especially after many corporate scandals and the failures of some biggest firms around the world such as Commerce Bank (1991) Enron (2001), Adelphia (2002), and World Com (2002). The aim of this study is to examine the relationship between board mechanisms (audit committee size, audit committee composition, board size, and board composition) and firm performance (ROA) based on the annual reports of listed companies in the year 2011 of sample of non-financial firms in the Saudi Market (Tadawul). For the purpose of this study, data was collected from a sample of 102 non-financial listed companies. Furthermore, an analysis of regression analysis is utilized to examine the relationship between board characteristics and firm performance. The results of this study reveal that audit committee size, audit committee composition and board size have no effect on firm performance in the selected sample while board composition has a significant negative relationship with firm performance.